Two new species of Cladosporium - DAS, ASHOK KUMAR (Indian Phytopathology, 2003)
Cladosporium chrysanthemi and C. desmodicola causing leaf spots on Chrysanthemum sp. and Desmodium gangeticum DC. Respectively were collected from West Bengal. These are described and illustrated in this paper. The type specimens have been deposited in the Herbarium, CAB, International Mycological Institute, UK.